Optimization of Dry Sliding Wear Parameters of Al 7075 MMC by Taguchi Method - Vajrala Venkata Reddy, K. Krishnamohan Reddy (Design Engineering, 2021)
The current study targetstowards optimize dry sliding wear parameters during wear studies of fly ash and silicon carbide reinforced Al 7075 alloy using the Taguchi method of experimental design. The Taguchi L9 design is chosen for the experiment design. Wear parameters such as applied load, sliding distance, and sliding speed are varied to see how they affect response wear rate and COF. Wear rate, according to Taguchi’s analysis, is more sensitive to load, whereas COF is heavily influenced by sliding velocity.